Extraction and chemical characterization of essential oil from eucalyptus obtained by microwave and ultrasound - Nolazco Cama, Diana (2020)
The solvent-free microwave extraction and the ultrasound-assisted extraction, as emerging technologies, offer advantages in the essential oil extraction, being the research about the effect on the yield and chemical composition of the essential oil important. The influence of leaves moisture and extraction power on the yield of solvent-free microwave eucalyptus essential oil, and a comparison with the ultrasound-assisted extraction was evaluated. The extraction was done by microwaves at 300 and 600 watts, 70, 80 and 90% humidity in the leaves, selecting the power that shows the highest yield of the essential oil. Afterwards, the effect of ultrasound at 180 watts, 40 kHz per 15 minutes on the yield and chemical composition was evaluated. The analytes obtained by both extraction methods were identified, by gas chromatography coupled to a mass spectrometer (GC-MS). The highest yield (0,55%) was obtained at 600 watts and 90% humidity by microwaves. The ultrasound-assisted extraction increased to 0,80% the yield and 17 analytes more in the essential oil. Eucalyptol or 1,8 cineol was identified as a major component, found in 42,43% and 37,15% corresponding to solvent- free microwave extraction and ultrasound-assisted extraction.